Frequent Dietetic Involvement Enhances Adherence and Clinical Outcomes of Exclusive Enteral Nutrition in Adults With Crohn's Disease - Matthew K. W. Chu; Alice S. Day; Damjana Bogatic; Martine Hatzi; Samuel K. S. Chu; Samuel P. Costello; Robert V. Bryant (JGH Open)
ABSTRACT Background and Aim Use of Exclusive Enteral Nutrition (EEN) in adults has been limited by lack of defined protocols, poor adherence and perceived lack of efficacy. This study evaluated EEN therapy in adults with Crohn's disease (CD) to identify determinants of clinical efficacy, adherence, and therapy completion. Methods This retrospective, multicenter study included consecutive adults (≥ 18 years old) prescribed EEN for CD between February 1, 2019, and February 28, 2022, at two tertiary teaching hospitals. The primary outcome was clinical remission (Harvey Bradshaw Index (HBI) ≤ 4) or response (HBI reduction ≥ 3). Therapy completion and adherence were measured. Intention‐to‐treat and per‐protocol analyses were performed. Results One‐hundred‐and‐eight patients were included; 54 (50.0%) were female. Mean age was 41.8 ± 16.1 years. Ileocolonic disease was present in 47.2% (51/108), and 40.7% (44/108) had stricturing phenotype. Baseline HBI was 8 (IQR 6–11); 60.2% (65/108) received advanced therapies. Among 80 patients treated for remission induction, remission and response rates were 50.0% (40/80) and 48.8% (39/80), respectively. Completion rate was 69.4% (75/108). Complete diet adherence was observed in 67.6% (73/108). On multivariable analysis, frequency of dietetic review was associated with therapy completion (odds ratio (OR) 2.26, 95% confidence interval (CI) 1.51–3.39, p < 0.001). Active smoking (OR 0.11, 95% CI 0.02–0.83, p = 0.032) reduced odds of remission, whereas early remission (OR 17.56, 95% CI 3.18–96.84, p = 0.001) and early response (OR 4.94, 95% CI 1.09–22.43, p = 0.039) were predictors of clinical remission at end‐of‐therapy. Conclusions Early assessment and frequent dietetic follow‐up improve EEN adherence, completion, and outcomes in adults with CD.